Ecological momentary interventions for eating disorders: a systematic review of the nascent science and recommendations for future research - Macarena Kruger; Jianyi Liu; Haley Graver; Stephanie Manasse; Elizabeth A. Velkoff (Journal of Eating Disorders)
Abstract Background Ecological momentary interventions (EMIs) deliver real-time, technology-based support in everyday settings. They have been used as standalone treatments or adjuncts to traditional care, with growing but still limited evidence supporting their effectiveness. EMIs offer a method for reducing barriers to care such as high costs, stigma, and limited access to providers – issues particularly relevant to eating disorder (ED) treatment, given the expense of inpatient care and the scarcity of specialized providers. This review examines existing research on EMIs for ED treatment, their design and content, and directions for future research. Methods We conducted a systematic review of EMI studies for EDs using PubMed, PsycINFO, Web of Science, and the Cochrane Library. Following screening for eligibility, we extracted data on study population, EMI design, and outcomes. Study quality was assessed using the Effective Public Health Practice Quality Assessment Tool (EPHPP). Results Our search identified 279 unique studies, of which eight met inclusion criteria. EMI notification content, timing, and delivery method varied across studies. Most studies included self-report or monitoring measures (7/8; 87.5%) to inform momentary delivery of tailored interventions. The effectiveness of EMIs showed mixed results. Of the two randomized-controlled trials included, both investigated EMIs as an adjunct to cognitive-behavioral therapy (CBT) and found that EMIs did not significantly enhance symptom reduction or skill acquisition beyond CBT alone. Studies testing EMI for maintaining treatment gains reported improvement in remission rates and symptom reduction, but poor adherence makes these results difficult to interpret. The average quality rating of the studies included was moderate. Conclusions Given the limited number of studies, we cannot draw broad conclusions about EMI effectiveness. We identified key gaps to address in future research, including examining moderators and mechanisms of EMI efficacy, refining EMI design to reduce participant burden, leveraging advanced technology for greater personalization of interventions, and recruiting larger and more diverse samples. Addressing these gaps will help clarify EMIs’ potential role in improving ED treatment.